2021
DOI: 10.1099/jgv.0.001595
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective screening of routine respiratory samples revealed undetected community transmission and missed intervention opportunities for SARS-CoV-2 in the United Kingdom

Abstract: In the early phases of the SARS coronavirus type 2 (SARS-CoV-2) pandemic, testing focused on individuals fitting a strict case definition involving a limited set of symptoms together with an identified epidemiological risk, such as contact with an infected individual or travel to a high-risk area. To assess whether this impaired our ability to detect and control early introductions of the virus into the UK, we PCR-tested archival specimens collected on admission to a large UK teaching hospital who retrospectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our study has several limitations. Prior exposure in our cohort involves only exposure to the lineage A or B variants (28,29), and natural infection by more antigenically diverse strains may skew the resultant immune potency and breadth. Unfortunately, we had too few positive PCR samples to try to elucidate any link between immunity and infecting lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. Prior exposure in our cohort involves only exposure to the lineage A or B variants (28,29), and natural infection by more antigenically diverse strains may skew the resultant immune potency and breadth. Unfortunately, we had too few positive PCR samples to try to elucidate any link between immunity and infecting lineage.…”
Section: Discussionmentioning
confidence: 99%
“…The first confirmed cases of COVID-19 in the UK were on the 29 th January 2020, when two Chinese nationals fell ill in York. The earliest known person to contract COVID-19 within the UK is believed to be a 75-year-old woman from Nottinghamshire, who tested positive on the 21 st February 2020 [ 22 ]. She is also understood to be the first victim of COVID-19 in the UK.…”
Section: Empirical Casementioning
confidence: 99%
“…The authors estimated that if the fifth version of the case definition had been applied throughout the outbreak, 4.2 times more confirmed cases would have been identified in China by February 20, 2020 (232,000 vs. 55,508). A more recent study benefitting from the availability of the complete genome sequence for SARS-CoV-2 and access to respiratory specimens collected early for retrospective analysis perhaps best demonstrates the effect of a restrictive case definition ( 23 ). Those authors identified multiple early cases of SARS-CoV-2 infection in Nottingham, UK, that, despite demonstrating symptoms consistent with COVID-19, did not meet case definition criteria used for diagnostic testing referral in place at the time because of lack of travel history or contact with an infected person.…”
Section: Discussionmentioning
confidence: 99%